Obstacle Negotiation, Gait Variability, and Risk of Falling: Results From the "Gait and Brain Study". (31st October 2018) - Pieruccini-Faria, Frederico; Montero-Odasso, Manuel
Abstract: Background: Gait variability is an early fall predictor. However, it is unknown how gait variability of older adults at high risk of falls is affected by an obstacle negotiation task. We aimed to compare gait performance between older adults with significant history of falls (i.e. fallers) and nonfallers while approaching an obstacle crossing. Methods: A total of 137 older adults without dementia were enrolled (72.7 ± 5.1 years of age; 60.5% women) from the "Gait and Brain Study." Fallers were defined as having at least one injurious fall or at least two noninjurious falls in the previous 12 months. Participants performed gait assessments under unobstructed and obstructed conditions. During the obstructed condition, participants walked and stepped over an ad hoc obstacle set at 15% of participants' height, transversally placed on a 6-meter electronic walkway. Gait speed and step-to-step variabilities were quantified from the last six steps prior to obstacle crossing. Analysis of variance models adjusted for age, sex, fear of falling, comorbidities, and unobstructed gait were used to compare gait performance of fallers and nonfallers during an obstacle approaching. Results: In the study, 27 older adults were identified as fallers and 110 as nonfallers. Fallers had higher step time variability and step length variability when approaching an obstacle compared with nonfallers, although groups had comparable gait performance during unobstructed walking. Conclusion: Gait variability of older individuals at high risk of falling is more disturbed, compared with low-risk individuals, while approaching an obstacle crossing. High gait variability prior to crossing an obstacle may be a risk factor for falls.